5x+12-(2x-12)=-3x+9

Simple and best practice solution for 5x+12-(2x-12)=-3x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+12-(2x-12)=-3x+9 equation:


Simplifying
5x + 12 + -1(2x + -12) = -3x + 9

Reorder the terms:
5x + 12 + -1(-12 + 2x) = -3x + 9
5x + 12 + (-12 * -1 + 2x * -1) = -3x + 9
5x + 12 + (12 + -2x) = -3x + 9

Reorder the terms:
12 + 12 + 5x + -2x = -3x + 9

Combine like terms: 12 + 12 = 24
24 + 5x + -2x = -3x + 9

Combine like terms: 5x + -2x = 3x
24 + 3x = -3x + 9

Reorder the terms:
24 + 3x = 9 + -3x

Solving
24 + 3x = 9 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
24 + 3x + 3x = 9 + -3x + 3x

Combine like terms: 3x + 3x = 6x
24 + 6x = 9 + -3x + 3x

Combine like terms: -3x + 3x = 0
24 + 6x = 9 + 0
24 + 6x = 9

Add '-24' to each side of the equation.
24 + -24 + 6x = 9 + -24

Combine like terms: 24 + -24 = 0
0 + 6x = 9 + -24
6x = 9 + -24

Combine like terms: 9 + -24 = -15
6x = -15

Divide each side by '6'.
x = -2.5

Simplifying
x = -2.5

See similar equations:

| 15X^4-(30X^2)(L^2)+7=0 | | 17x+14y=930 | | 12x+53=9x+15+x | | 9x+3=-53+2x | | x+48=-5x | | 3x-0.79=1.2+2x | | Cotx=3.45 | | 2(5x-1)=7(x+4) | | Cora=3.45 | | 70=-22.81 | | -5x-2=7x-4 | | 5(2x+y+2)+12(y-1)= | | 6(c+2d+7)+2(7c-5)= | | 5(2x+3y)+2(4-x-2y)+1= | | 6z+4=-4 | | 24Z=0 | | 8(x+y)+7(2x+3y)= | | 19a-8-12a+17= | | 11x-5-3x-9= | | x+2y+3z=26 | | 5(P+5)-3(P-1)=32 | | 6e+8f+(-2)e+16f= | | 6ln(5x-1)=3 | | 2x+4-3=2x+1 | | 8h-3-5h-4= | | 0.25(y+2)-0.15(y+3)=4 | | (-7)y+8+15y-14= | | 45x^3-5x+0=0 | | 10x^2-16+6=0 | | [4-(2-4(2-4)+6)]+3=-9 | | 0=-4+x^2 | | 0=4+x*x |

Equations solver categories